2011
DOI: 10.1002/eji.201040868
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human T‐cell functions by reactive nitrogen species

Abstract: Previous studies have suggested that T-lymphocyte dysfunction might be attributable to nitrative stress induced by reactive nitrogen species (RNS). In this manuscript, we explored this hypothesis and provided a direct demonstration of the inhibitory effects of RNS on human T-cell signaling, activation, and migration. We found that short exposure of human T cells to RNS induced tyrosine phosphorylation of several proteins, including the CD3f chain of the TCR complex, and release of Ca 21 from intracellular stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…These include production of reactive oxygen and nitrogen species (ROS & RNS) that are generated by the inducible nitric oxide synthase (iNOS) and NADPH oxidase enzymes, and depletion of key nutrients required for normal function of T-cells, especially arginine by activation of arginase, and tryptophan and cysteine by sequestration in tumor-specific T-cells 16 . Additionally, activation of T-cells can be impaired by nitration of their antigen or chemokine receptors 7 , or suppressed by induction of T regulatory cells via TGF-β produced by MDSC. 8 …”
Section: Introductionmentioning
confidence: 99%
“…These include production of reactive oxygen and nitrogen species (ROS & RNS) that are generated by the inducible nitric oxide synthase (iNOS) and NADPH oxidase enzymes, and depletion of key nutrients required for normal function of T-cells, especially arginine by activation of arginase, and tryptophan and cysteine by sequestration in tumor-specific T-cells 16 . Additionally, activation of T-cells can be impaired by nitration of their antigen or chemokine receptors 7 , or suppressed by induction of T regulatory cells via TGF-β produced by MDSC. 8 …”
Section: Introductionmentioning
confidence: 99%
“…We then investigated whether the presence of reactive nitrogen plays a role in the differential distribution of CD8 + T cells within fibrous septa and tumor lobules (31). Staining with the nitrotyrosine-specific mAb showed that the T-lymphocyte distribution mirrored the nitrotyrosine staining (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of iNOS in the generation of Tlymphoctye-derived NO and its role in inhibiting T lymphocyte proliferation have been documented (108,135). Vig et al have shown that iNOS production in activated T cells regulates T-cell death and immune memory (295).…”
Section: Interestingly Studies Indicate a Role Of Mnsod Inactivationmentioning
confidence: 99%